Targeting cortical representations in the treatment of chronic pain: a review - Moseley, G. Lorimer; Flor, Herta (Neurorehabilitation and neural repair, 2012)
Recent neuroscientific evidence has confirmed the important role of cognitive and behavioral factors in the development and treatment of chronic pain. Neuropathic and musculoskeletal pain are associated with substantial reorganization of the primary somatosensory and motor cortices as well as regions such as the anterior cingulate cortex and insula. What is more, in patients with chronic low back pain and fibromyalgia, the amount of reorganizational change increases with chronicity; in phantom limb pain and other neuropathic pain syndromes, cortical reorganization correlates with the magnitude of pain. These findings have implications for both our understanding of chronic pain and its prevention and treatment. For example, central alterations may be viewed as pain memories that modulate the processing of both noxious and nonnoxious input to the somatosensory system and outputs of the motor and other response systems. The cortical plasticity that is clearly important in chronic pain states also offers potential targets for rehabilitation. The authors review the cortical changes that are associated with chronic pain and the therapeutic approaches that have been shown to normalize representational changes and decrease pain and discuss future directions to train the brain to reduce chronic pain.
Gesehen am 17.05.2018